The Organizational Decision Making in an Administrative Reform Process. A e-Government Case Study in a Mexican Municipality - Quinteros Castellano, Carlos (Estado, Gobierno y Gestión Pública, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>